2016
DOI: 10.1007/s00244-016-0289-1
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Colonization and Survival of E. coli from Varying Host Sources in Drainage Basin Sediments and Stormwater

Abstract: It is widely understood that stormwater drainage has a significant impact on the health of tidal creek systems via regular inputs of runoff from the surrounding watershed. Due to this hydrologic connection, contamination of the upstream drainage basin will have a direct effect on estuaries and tidal creeks that often act as receiving waters. This study focuses on the importance of drainage basin sediments as they enhance the persistence and transport of the fecal indicator bacteria E. coli within a watershed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In these studies, decay of E. coli and enterococci from cattle, bovine, deer, goose, and ovine feces was considerably slower than that of organisms originating from sewage (27,175) or human feces (36,176). In contrast, FIB from dog (9) and seagull (121,129) feces decayed more rapidly than those from sewage and human feces. FIB isolated from environmental water, soil, and sediments typically decayed more slowly than FIB from sewage (9) or organisms originating from dog, bovine, deer, or goose feces (9,87).…”
Section: Intrinsic Factorsmentioning
confidence: 92%
See 3 more Smart Citations
“…In these studies, decay of E. coli and enterococci from cattle, bovine, deer, goose, and ovine feces was considerably slower than that of organisms originating from sewage (27,175) or human feces (36,176). In contrast, FIB from dog (9) and seagull (121,129) feces decayed more rapidly than those from sewage and human feces. FIB isolated from environmental water, soil, and sediments typically decayed more slowly than FIB from sewage (9) or organisms originating from dog, bovine, deer, or goose feces (9,87).…”
Section: Intrinsic Factorsmentioning
confidence: 92%
“…In a rare consensus, all the studies comparing decay in sediments versus the overlying water column found extended persistence in sediments. This finding applied to culturable FIB (fecal coliforms, E. coli, and enterococci) (9,45,69,85,88,104,(119)(120)(121)(122), FIB quantified by qPCR (Entero1a and uidA) (69,104), a variety of MST markers (BacCan, BacCow, BacHum, and LA35) (69,104), and bacterial pathogens quantified by both culture and qPCR (Campylobacter coli, E. coli O157:H7, Salmonella spp., and Vibrio parahaemolyticus) (69,120,122). The trend was also consistent regardless of the water type (i.e., freshwater or marine water), experimental design (outdoor or indoor), or inoculum source (strains, human and other animal fecal material, or organisms indigenous to aquatic habitats).…”
Section: Alternative Habitatsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the effect of ambient sunlight, salinity (and the associated ionic content of brackish and marine waters) affected the decay rates of culturable/infectious FIB, alternative indicators, MST markers and pathogens more so than their corresponding nucleic acids [168,169,170,171,172,173,174]. The effect of source of fecal pollution has been studied on FIB and MST markers, and indicators originating from ruminants are more persistent compared to those from other fecal sources (e.g., dog, seagull, and human) [169,175,176,177,178,179], although different human sources (e.g., feces, septage, and sewage) elicit different decay rates [152]; analogous information for alternative indicators and pathogens is still missing. Finally, studies that compared decay of various indicators to pathogens directly under the same experimental conditions are rare and report conflicting results.…”
Section: Susceptibility To Environmental Stressorsmentioning
confidence: 99%